2014
DOI: 10.1111/ijlh.12222
|View full text |Cite
|
Sign up to set email alerts
|

Tracking down contact activation – from coagulation in vitro to inflammation in vivo

Abstract: Summary The contact system is a volatile and versatile enzyme system in blood plasma that responds to the presence of nonphysiological surface materials by spontaneous generation of enzymatic activity. In subsequent steps, it can trigger blood coagulation and is responsible for the generation of the proinflammatory peptide bradykinin. The physiological role of the contact system is presently unknown, but it is commonly used to trigger coagulation in a diagnostic setting. In this three‐part review, we will firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 49 publications
(53 reference statements)
0
41
0
1
Order By: Relevance
“…The zymogens FXII and PK and the non-enzymatic cofactor HK comprise the plasma kallikrein-kinin system [14]. FXII was identified as a plasma constituent missing in a patient with a defect in surface-induced plasma coagulation, but with no symptoms of a bleeding disorder [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The zymogens FXII and PK and the non-enzymatic cofactor HK comprise the plasma kallikrein-kinin system [14]. FXII was identified as a plasma constituent missing in a patient with a defect in surface-induced plasma coagulation, but with no symptoms of a bleeding disorder [25].…”
Section: Discussionmentioning
confidence: 99%
“…FXII was identified as a plasma constituent missing in a patient with a defect in surface-induced plasma coagulation, but with no symptoms of a bleeding disorder [25]. It is now clear that FXII is not required for hemostasis [14,25]. While relatively few patients with PK or HK deficiency have been described, these conditions, like FXII deficiency, are not associated with a bleeding diathesis [25,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 33 In vitro activation of the contact system is used to measure activated partial thromboplastin time (aPTT), while the best characterized event associated with its in vivo activation is angioedema due to C1-INH deficiency. It has been shown that the increase in BK plasma levels during attacks is due to local production of BK as a result of inappropriate activation of systems controlled by C1-INH.…”
Section: Mechanisms Of Edema Formationmentioning
confidence: 99%
“…43 Experimental results have shown that FXII may pivot contact system activation in vivo similar to the mechanism observed in vitro, suggesting that the enzymatic activity of FXII may initiate contact activation. 33,44 Moreover, other studies have shown that FXII can be activated in vivo by substances such as platelets polyphosphates and heparin-activated mast cells, thus ensuring efficient activation of the contact system. 45,46 Thus, it is possible that these mechanisms of contact activation specifically contribute to angioedema formation.…”
Section: Mechanisms Of Edema Formationmentioning
confidence: 99%